Patterns of dietary supplement use among college students. Issue 5 (October 2015) - Lieberman, Harris R.; Marriott, Bernadette P.; Williams, Christianna; Judelson, Daniel A.; Glickman, Ellen L.; Geiselman, Paula J.; Dotson, Laura; Mahoney, Caroline R.
Summary Background & aims Dietary supplements (DS) are popular in many countries but little data are available on their use by sub-populations such as college students. Since students share a variety of characteristics and similar lifestyles, their DS use may differ from the general population. This study assessed DS use, factors associated with DS use, and reasons for use among U.S. college students. Methods College students (N = 1248) at 5 U.S. universities were surveyed. Survey questions included descriptive demographics, types and frequency of DS used, reasons for use and money spent on supplements. Supplements were classified using standard criteria. Logistic regression analyses examined relationships between demographic and lifestyle factors and DS use. Results Sixty-six percent of college students surveyed used DS at least once a week, while 12% consumed 5 or more supplements a week. Forty-two percent used multivitamins/multiminerals, 18% vitamin C, 17% protein/amino acids and 13% calcium at least once a week. Factors associated with supplement use included dietary patterns, exercise, and tobacco use. Students used supplements to promote general health (73%), provide more energy (29%), increase muscle strength (20%), and enhance performance (19%). Conclusions College students appear more likely to use DS than the general population and many use multiple types of supplements weekly. Habits established at a young age persist throughout life. Therefore, longitudinal research should be conducted to determine whether patterns of DS use established early in adulthood are maintained throughout life. Adequate scientific justification for widespread use of DS in healthy, young populations is lacking.